A SMART BABY CRADLE SYSTEM BASED ON IOT - Javlon Tursunov (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
this thesis proposes the development of a software and hardware complex for a Smart House element, specifically a Smart Baby Cot. The project involves the use of heuristic models and incorporates both Wi-Fi and GSM modules to extend the range and facilitate communication. The baby cot can be controlled through an Android app, offering both manual and automatic control options, making it a truly smart device. This work fills a research gap as most Smart House and IoT projects do not incorporate the use of both Wi-Fi and GSM modules. To support the proposed work, this literature review explores the latest developments in Smart House Development and related sensors. Through the review of some of the latest references, the potential benefits of the proposed Smart Baby Cot are highlighted, including increased convenience and control through the use of mobile devices and the ability to facilitate communication through the use of both Wi-Fi and GSM. Overall, this work presents a novel approach to Smart House elements, specifically in the area of baby monitoring, and holds significant potential for improving the quality of life for parents and caregivers.